2024
DOI: 10.3390/life14030369
|View full text |Cite
|
Sign up to set email alerts
|

The Global Decline in Human Fertility: The Post-Transition Trap Hypothesis

Robert John Aitken

Abstract: Over the past half a century many countries have witnessed a rapid fall in total fertility rates, particularly in the world’s most advanced economies including the industrial powerhouses of Eastern Asia and Europe. Such nations have now passed through the first and second demographic transitions and are currently exhibiting fertility rates well below the replacement threshold of 2.1, with no sign of recovery. This paper examines the factors responsible for driving these demographic transitions and considers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…Because MP research is a recent field of study, longterm and transgenerational health studies have yet to be completed, resulting in a knowledge gap in human health risks (Kirstein et al, 2021). However, it has already been shown that plastic leachates can cause reproductive disruption (Akoueson et al, 2023), potentially linked to the world's decreasing fertility rates (Aitken, 2024). We also know that adjacency to plastic production or discarding-sites can have serious health effects including cancer (Landrigan et al, 2023).…”
Section: Microplastic Toxicity In Humansmentioning
confidence: 99%
“…Because MP research is a recent field of study, longterm and transgenerational health studies have yet to be completed, resulting in a knowledge gap in human health risks (Kirstein et al, 2021). However, it has already been shown that plastic leachates can cause reproductive disruption (Akoueson et al, 2023), potentially linked to the world's decreasing fertility rates (Aitken, 2024). We also know that adjacency to plastic production or discarding-sites can have serious health effects including cancer (Landrigan et al, 2023).…”
Section: Microplastic Toxicity In Humansmentioning
confidence: 99%
“…The importance of maintaining the fertility rate at its natural pro le is vital issue for human healthcare, wellbeing, and race continuity; otherwise, any fertility decline will have negative impact on both current and future healthcare, socioeconomic balance and hence pose a threat for human race existence [1,10].…”
Section: Introductionmentioning
confidence: 99%